Membangun Kemampuan Koneksi Matematika melalui Strategi Interaksi Peserta Didik Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Institut Agama Islam Negeri (IAIN) Jember: Building Mathematical Connection Skills through Student Interaction Strategies in the Primary Teacher Education Program (PGMI) at the State Islamic Institute (IAIN) Jember - Mohammad Kholli (Fenomena, 2016)
Learning as a student activity becomes more effective when interaction occurs, whether among students, between students and educators constructively, or between students and learning resources and tools. Through interaction, students can observe, listen, reason, and engage in activities that allow them to construct new knowledge and learning experiences. Learning with interaction strategies to build mathematical connection skills is implemented in three stages: preliminary activities, core activities, and closing activities. In these stages, educators perform several actions to achieve the objectives. Learning with interaction strategies can build mathematical connection skills among D1-grade students in the PGMI program at IAIN Jember, with 80% of students able to connect the concepts of equations and inequalities and apply them in daily life. Overall, the learning outcomes achieved classical completeness, where 93% of students scored 70 or above, with an average score of 81.7. Pembelajaran sebagai aktivitas peserta didik akan lebih efektif jika terjadi interaksi, baik antar peserta didik, antara peserta didik dengan pendidik secara konstruktif, maupun peserta didik dengan sumber dan alat belajar. Melalui interaksi, peserta didik dapat melihat, mendengar, bernalar, dan melakukan aktivitas yang memungkinkan mereka mengonstruksi pengetahuan dan pengalaman belajar baru. Pembelajaran dengan strategi interaksi yang dapat membangun kemampuan koneksi matematika dilaksanakan dalam tiga tahap: kegiatan pendahuluan, inti, dan penutup. Pada ketiga tahap tersebut, terdapat beberapa tindakan yang dilakukan pendidik untuk mencapai tujuannya. Pembelajaran dengan strategi interaksi dapat membangun kemampuan koneksi matematika peserta didik kelas D1 di Prodi PGMI IAIN Jember, yaitu 80% peserta didik mampu menghubungkan konsep persamaan dan pertidaksamaan serta menggunakannya dalam kehidupan sehari-hari. Secara keseluruhan, hasil pembelajaran telah mencapai ketuntasan belajar klasikal, di mana 93% peserta didik mencapai nilai hasil belajar 70 atau lebih, dengan rata-rata nilai 81,7.